2023
DOI: 10.3390/toxins15120691
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Botulinum Toxin Doses on Nerve Regeneration in Rats with Experimentally Induced Sciatic Nerve Injury

Seokjoon Hwang,
Minsu Seo,
Tae Heon Lee
et al.

Abstract: This study was designed to compare the effects of various doses of botulinum neurotoxin A (BoNT/A) on nerve regeneration. Sixty-five six-week-old rats with sciatic nerve injury were randomly allocated to three experimental groups, a control group, and a sham group. The experimental groups received a single session of intraneural BoNT/A (3.5, 7.0, or 14 U/kg) injection immediately after nerve-crushing injury. The control group received normal intraneural saline injections after sciatic nerve injury. At three, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Notably, suppression of neuroinflammation has been proposed to facilitate neurogenesis, synaptic plasticity, and neuroprotection in the brain. (Hwang et al 2023), Therefore, the increased number of immature neurons observed in the hippocampus of BoNT-treated groups could be attributed to BoNT-mediated neurotrophic support and its anti-neuroinflammatory properties.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Notably, suppression of neuroinflammation has been proposed to facilitate neurogenesis, synaptic plasticity, and neuroprotection in the brain. (Hwang et al 2023), Therefore, the increased number of immature neurons observed in the hippocampus of BoNT-treated groups could be attributed to BoNT-mediated neurotrophic support and its anti-neuroinflammatory properties.…”
Section: Discussionmentioning
confidence: 95%
“…Wang, L reported that following 48 hours of treatment with BoNT, SH-SY5Y cells exhibit induced expression transcripts related to neuronal cell development and metabolic processes (Wang et al 2020). BoNT has been shown to up-regulate the level of brain-derived neurotrophic factor (BDNF), which is a crucial neurotrophin involved in the differentiation, neuron survival, and synaptic plasticity of newborn neurons in the adult brain (Hwang et al 2023), Therefore, the increased number of immature neurons observed in the hippocampus of BoNT-treated groups could be attributed to BoNT-mediated neurotrophic support and its anti-neuroinflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved in muscle recovery after (repeated) injections with BoNT-A are not well understood. In an experimental nerve injury model, BoNT-A has been shown to accelerate axonal growth and increase the regeneration of myelinated fibers [ 56 ] while also releasing neurotrophic factors [ 57 ]. Spontaneous recovery from BoNT-A-induced gastrocnemius muscle atrophy in mice is associated with a strong upregulation of the mTOR/S6 kinase signaling pathway with the upregulation of myotrophic factors such as IGF-I and IGF-II [ 58 ].…”
Section: Discussionmentioning
confidence: 99%